2008
DOI: 10.1021/ie070647t
|View full text |Cite
|
Sign up to set email alerts
|

SO3H-Functionalized Ionic Liquids for Selective Alkylation of p-Cresol with tert-Butanol

Abstract: The SO3H-functionalized ionic liquids were synthesized by using pyridine and 1,4-butane or 1,3-propane sulfone as the source and characterized by NMR and time-of-flight mass spectrometry. The acidity of the ionic liquids determined by the Hammett method is almost the same as that of a conventional acid, such as H2SO4. The catalytic performance of ionic liquids for the tert-butylation of p-cresol with tert-butanol was evaluated; by using the ionic liquids as catalysts at the optimum reaction conditions, 79% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…This indicated that the increase in temperature mainly cause the O-alkylated product turned into 2-TBC and further C-alkylation of 2-TBC with TBA. With the increasing of reaction time, the conversion of p-cresol and the selectivity of 2-TBC increase rapidly and reach a maximum after 6 h. Continued to increase in reaction time, the selectivity of 2,6-DTBC improves gradually, but the conversion of p-cresol almost remains constant, which agrees with the results reported in literature (16,17). The influence of amount of BAILs on the conversion of p-cresol and Green Chemistry Letters and Reviews 181 the selectivity of 2-TBC was also discussed ( Table 5).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This indicated that the increase in temperature mainly cause the O-alkylated product turned into 2-TBC and further C-alkylation of 2-TBC with TBA. With the increasing of reaction time, the conversion of p-cresol and the selectivity of 2-TBC increase rapidly and reach a maximum after 6 h. Continued to increase in reaction time, the selectivity of 2,6-DTBC improves gradually, but the conversion of p-cresol almost remains constant, which agrees with the results reported in literature (16,17). The influence of amount of BAILs on the conversion of p-cresol and Green Chemistry Letters and Reviews 181 the selectivity of 2-TBC was also discussed ( Table 5).…”
Section: Resultssupporting
confidence: 91%
“…BAILs-1 and -2 exhibited higher acidity than H 2 SO 4 and single SO 3 H-functionalized BAIL-3 (16), , and BAIL-5 (17) due to the double sulfonic acid groups on cations and two or three acidic HSO 4 − anions in their structure ( Table 1). The content of water in BAILs-1 and -2 ranges from 2.0% to 2.5% (Karl-Fischer titration).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, catalysts having a mesoporous structure, such as polystyrene based Amberlyst-15 and Purolite 500, showed higher EL yield (>80 %) and lesser DEE formation due to greater accessibility of acid sites to FAL as compared to ethanol 101,102 , Table- Table-3 BMIm IL (Hammet Acidity = 2.5) and comparable to other conventional acids (H2SO4) 108 .…”
Section: Synthesis Of El From Falmentioning
confidence: 97%
“…ILs have also been designed to be Brønsted acids by covalently tethering an acid group on the cationic part of the ionic liquids [16,17]. Sulfonic or carboxylic acids have for example been grafted on the imidazolium cation leading to functionalized "Task-Specific-Ionic Liquids" [18,19]. …”
mentioning
confidence: 99%